Determining Factors for Improving the Performance of Commitment Making Officials (PPK) in the Kerinci Regency APBD Project - Alek Irawan Triantho; Tomi Apra Santosa (Indonesia Journal of Engineering and Education Technology (IJEET), 2023)
The problems that occurred in Kerinci Regency are considered incomplete in the work of PPK (Commitment Making Officer) Paragraph 1 Perpres No. 16 of 2018 regulates the preparation of the purchase plan, meaning that the PPK task is very important. deadline for preparation for the purchase plan. If the planning is delayed, then the action will automatically begin to be late. This study analyzes: 1. Determinants of PPK activities in Kerinci Regency. 2. Factors that influence the improvement of PPK performance in the Kerinci Regency APBD 3. Finding solutions and suggestions to improve PPK performance in the Kerinci Regency APBD. The results of this study are as follows: 1. In the Kerinci Regency APBD, 9 factors that influence PPK performance are the ability, motivation, skills, knowledge, leadership, people, skills, confidentiality and care. 2. The dominant factor that affects the performance of the Kerinci Regency APBD PPK officers is a skill factor. 3. Solutions that can be given to increase the effectiveness of PPK are: a) Improve the ability of PPK officials to carry out their duties. b) Providing good motivation to PPK officials, so that PPK can encourage them positively in carrying out their duties; c) Assist PPK officials in the development of knowledge, skills and abilities as well as individuals or personality; d) Give the authority and responsibility to PPK and its staff to carry out and regulate themselves without interference and influence from the local government in carrying out their duties.